Smart Fertigation Control System of Plantation Chili in Greenhouse - Lee, Lee chee wei; Ramhuzaini Abd Rahman (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The Smart Fertigation Control System has gained significant attention in greenhouses due to its potential to enhance crop management and ensure agricultural sustainability in chili (Capsicum annuum) plantations. This study aimed to develop a smart fertigation system for chili plantations, investigate suitable control schemes, and evaluate the effectiveness of these schemes compared to traditional methods. An experimental approach was employed to compare two types of controllers, Bang-bang and PID, for delivering two different types of fertilizer into a mixing tank. The experiment, conducted using Arduino IDE software, applied the formulations of these controllers to achieve sustainable fertilizer delivery. Results indicate that the PID controller is more effective and sustainable in controlling the system compared to the Bang-bang controller. The primary variable in this study was the pH setpoint, with the goal of mixing two fertilizers with low and high pH to achieve a pH of 7.5. Maintaining a constant pH value as shown on the serial monitor was essential throughout the research. The findings suggest that the PID controller significantly improves the growth and sustainability of chili plants compared to traditional fertigation methods.